Association between self-reported multimorbidity and longitudinal brain Aβ deposition in Alzheimer’s disease - Xian-Le Bu; Wei Zhu; Qing-Hua Wang; Zhuo-Ting Liu; Yun-Yu Bao; Yu-Di Bai; Jiang-Hui Li; Zhi-Hao Liu; Jia-Ling Zhao; Yang Xiang; Wang-Sheng Jin; Jun Wang; et al. (Nature Communications)
Abstract Multimorbidity is common in older adults. However, whether multimorbidity accelerates brain beta-amyloid (Aβ) deposition, the molecular driver of Alzheimer’s disease (AD), in humans remains largely unknown. In this study, we selected 435 brain Aβ-positive participants with available longitudinal Aβ-PET data (mean duration 3.9 years) from the Alzheimer’s Disease Neuroimaging Initiative (ADNI) cohort. Twenty-two self-reported chronic disorders were considered as a measure of the severity of multimorbidity. After adjustment for age, sex, education level, APOE-ε4 status and baseline cognitive state, individuals with a high or medium multimorbidity burden had faster rates of brain Aβ accumulation than individuals with a low multimorbidity burden. Moreover, both the central nervous system and peripheral system multimorbidity burdens were associated with longitudinal brain Aβ deposition. These results indicate that peripheral organ and tissue dysfunctions may contribute to AD pathogenesis, which may help researchers better understand AD pathogenesis and tailor interventions for AD from a systemic view.